Idiopathic REM Sleep Behavior Disorder: Implications for the Pathogenesis of Lewy Body Diseases - Tomoyuki Miyamoto; Masayuki Miyamoto; Masaoki Iwanami; Koichi Hirata (Parkinson's Disease, 2011)
Objectives. Both results of the odor identification and cardiac 123I-metaiodobenzylguanidine accumulation have been investigated for their potential to enhance the detection of pathogenesis resembling that of Lewy body-related α-synucleinopathies in patients clinically diagnosed as having idiopathic REM sleep behavior disorder. Methods. We performed both the Odor Stick Identification Test for Japanese and 123I-metaiodobenzylguanidine scintigraphy in 30 patients with idiopathic REM sleep behavior disorder, 38 patients with Parkinson's disease, and 20 control subjects. Results. In idiopathic REM sleep behavior disorder, reduced odor identification score and an early or delayed heart to mediastinum ratio on 123I-metaiodobenzylguanidine were almost as severe as in Parkinson's disease patients. Delayed cardiac 123I-metaiodobenzylguanidine uptake was even more severe in the idiopathic REM sleep behavior disorder group than in the Parkinson's disease group. Conclusions. Reduced cardiac 123I-metaiodobenzylguanidine uptake, which is independent of parkinsonism, may be more closely associated with idiopathic REM sleep behavior disorder than olfactory impairment.